Industrial Revolution 4.0: A Case Study On Character Building For Arabic Teaching At Islamic Boarding School In Indonesia - Sopian, Asep; Sanusi, Anwar; Nurkomala, Rima (Ijaz Arabi Journal of Arabic Learning, 2024)
In the industrial revolution era, good teaching and learning processes should integrate the transfer of knowledge and values as a solid foundation for building students’ character. This research is a descriptive case study; the data were collected using observations and interviews before they were analyzed using an interactive model proposed by Miles & Huberman (1994). The result shows that Arabic teaching and learning is a befitting school subject that instills character values. Furthermore, character building can be seen in the planning, implementing, and evaluating Arabic teaching and learning processes. However, obstacles to its processes still exist, including the lack of coordination between parents and educators in the Islamic boarding school environment. Its supporting factors were also found, including a supportive curriculum, positive habituation, support for adequate facilities and infrastructure, and various programs organized by the Islamic boarding school regarding building the student character.